Remembering Dr. Jorge Ascenzo-Cabello. - Ascenzo Palacio, Alberto (2015)
Dr. Jorge Ascenzo Cabello’s biographical sketch recalls his pioneering work in the study of Peruvian couples suffering of sterility and infertility. He founded in Lima the Peruvian Fertility Institute, a center devoted to the care of couples with reproduction problems and training of young physicians. He was Founding President of the Peruvian Fertility Society, among other distinguished society positions and devoted his life to clinical care in reproduction.